2014
DOI: 10.1113/jphysiol.2013.270280
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial cerebellar direct current stimulation and transcutaneous spinal cord direct current stimulation as innovative tools for neuroscientists

Abstract: Two neuromodulatory techniques based on applying direct current (DC) non-invasively through the skin, transcranial cerebellar direct current stimulation (tDCS) and transcutaneous spinal DCS, can induce prolonged functional changes consistent with a direct influence on the human cerebellum and spinal cord. In this article we review the major experimental works on cerebellar tDCS and on spinal tDCS, and their preliminary clinical applications. Cerebellar tDCS modulates cerebellar motor cortical inhibition, gait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 118 publications
2
96
0
1
Order By: Relevance
“…The effect was specific because SEPs elicited by median nerve stimulation were not influenced by thoracic transcutaneous spinal DC stimulation. Several further studies replicated the observation that weak DC delivered over the spinal cord can influence different physiological variables of spinal cord function in humans and animals, both intact and injured (for a review see (Priori et al 2014). …”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 70%
See 3 more Smart Citations
“…The effect was specific because SEPs elicited by median nerve stimulation were not influenced by thoracic transcutaneous spinal DC stimulation. Several further studies replicated the observation that weak DC delivered over the spinal cord can influence different physiological variables of spinal cord function in humans and animals, both intact and injured (for a review see (Priori et al 2014). …”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 70%
“…Like tDCS, spinal DC often elicits short-lasting tingling sensations when stimulation begins and ends, and sometimes redness under the electrode. The effect of polarity on physiology is complex (Priori et al 2014). In general, in humans it can be assumed that thoracic transcutaneous DC under the anode electrode decreases responses involving spinal tract compartments below the stimulating electrode and increases segmental reflex responses, whereas the cathode electrode induces opposite effects.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, of the few studies which reported significant effects of tDCS applied on SMA, two (Kwon & Kwon, 2013;Vollmann et al, 2013) With regards to the after-effects, many studies highlighted that the changes in excitability not only developed during DC stimulation, but lasted for several minutes or hours after its end. This effect was observed on several cortical and sub-cortical areas (Polania et al, 2012;Monte-Silva et al, 2013;Bolzoni et al, 2013a,b;Nonnekes et al, 2014;Priori et al, 2014) and also on the spinal cord (Cogiamanian et al, 2008;Ahmed, 2013;Priori et al, 2014). The after-effects are likely mediated by mechanisms of synaptic long-term potentiation and depression, which affect neuroplasticity (Nitsche et al, 2002;Ahmed, 2013;Monte-Silva et al, 2013).…”
Section: Some Considerations About Tdcs On Smamentioning
confidence: 81%